2016
DOI: 10.1371/journal.pone.0143578
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Light Exposure Is Associated with Increased Body Mass in Children

Abstract: The timing, intensity, and duration of exposure to both artificial and natural light have acute metabolic and physiological effects in mammals. Recent research in human adults suggests exposure to moderate intensity light later in the day is concurrently associated with increased body mass; however, no studies have investigated the effect of light exposure on body mass in young children. We examined objectively measured light exposure and body mass of 48 preschool-aged children at baseline, and measured their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 54 publications
(74 reference statements)
0
18
0
Order By: Relevance
“…A similar link has been observed in humans, since the prevalence of attentiondeficit/hyperactivity-disorder (ADHD) is lower in geographical areas with high levels of sunlight exposure (Arns, van der Heijden, Arnold, & Kenemans, 2013). Daylight is the principal cue for biological rhythms entrainment in all species (Cao et al, 2015) and is implicated in endocrine (Middleton, Arendt, & Stone, 1997;Scheer & Buijs, 1999), metabolic (Pattinson et al, 2015;Reid et al, 2014), circadian , and cognitive functioning (Cajochen, 2007;Vandewalle, Maquet, & Dijk, 2009).…”
Section: Daylight Exposurementioning
confidence: 56%
See 1 more Smart Citation
“…A similar link has been observed in humans, since the prevalence of attentiondeficit/hyperactivity-disorder (ADHD) is lower in geographical areas with high levels of sunlight exposure (Arns, van der Heijden, Arnold, & Kenemans, 2013). Daylight is the principal cue for biological rhythms entrainment in all species (Cao et al, 2015) and is implicated in endocrine (Middleton, Arendt, & Stone, 1997;Scheer & Buijs, 1999), metabolic (Pattinson et al, 2015;Reid et al, 2014), circadian , and cognitive functioning (Cajochen, 2007;Vandewalle, Maquet, & Dijk, 2009).…”
Section: Daylight Exposurementioning
confidence: 56%
“…For example, the outdoor environment offers opportunities for unrestricted play and physical activity , fresh air, learning experiences (Maynard & Waters, 2007), attention restoration (Ohly et al, 2016), and daylight exposure (Ancoli-Israel et al, 1997). In turn, exposure to these elements may protect against a host of health problems (Pate et al, 1995;Pattinson, Allan, Staton, Thorpe, & Smith, 2015).…”
Section: The Natural Environmentmentioning
confidence: 99%
“…Importantly, changes in daily light exposure duration are pertinent to metabolic health. Human studies have shown that exposure to light at night correlates to a higher body weight (McFadden et al, 2014;Rybnikova et al, 2016) and prolonged duration of environmental light exposure predicts increased weight gain in children (Pattinson et al, 2016). We previously identified impaired BAT activity as the potential missing link in the established association between perturbations in circadian rhythms and metabolic disorders by demonstrating that prolonged daily light exposure reduces BAT activity and induces adiposity in mice (Kooijman et al, 2015a).…”
Section: Discussionmentioning
confidence: 99%
“…The study, commencing in 2004, found children aged 4–5 years were getting, on average, 10 h 55 m sleep per night, a finding consistent with the recommendations of the US National Sleep Foundation for this age group . Another Australian study measured sleep in children aged 3–5 years using actigraphy and found that children sleep an average of 9.6 h across the day . However, the proportion of pre‐school‐aged children meeting sleep duration recommendations in Australia is unknown.…”
mentioning
confidence: 80%